From hell being a melodrama in sixteen parts - Moore, Alan 1953- (Top Shelf Productions, 2006)
Dramatizes the Jack the Ripper murders in graphic novel form, and includes author commentary and an appendix, "Dance of the Gull Catchers." Contains adult content